Analyzing corruption possibilities in the gaze of the media - Samarth Vaidya (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2001)
In this paper I analyze the economic incentives that govern the strategic relationship between the government and the independent media using a consistent analytical framework. The analysis focuses on the extent to which the `free' press can act as a deterrent to corruption in governance. I find that although `press freedom' is indeed important as stressed in the existing literature, both mutually profitable cover-up arrangements as well as the government's ability to `manage' the media's allegations tend to have a substantial negative impact on the media's role as an effective watchdog. Also, more competition in the media sector need not necessarily translate into increased deterrence from corruption. – media ; corruption ; political accountability ; governance ; contest
Keywords: D72; D74; D78; H57; K40; 330; Public Choice; Meinungsfreiheit; Theorie